2015
DOI: 10.1016/j.wear.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inclusion composition on tool wear in hard part turning using PCBN cutting tools

Abstract: This work reports on hard part turning of carburizing steels using a PCBN cutting tool in fine machining. Emphasis is on the link between composition of the inclusions in work material and wear mechanisms of the cutting tool. A Ca-treated machinability improved 20NiCrMo steel was included together with three other carburizing steels with different inclusion characteristics. Machining tests were conducted to examine cutting tool life and its balance between excessive flank wear or crater wear. The wear mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The main wear mechanism was abrasion wear [17], causing crater wear resulting in final cutting edge failure. Similar wear mechanisms were observed by the authors in references [18,19] in high speed machining of hardened steel. W.Y.H.…”
Section: Introductionsupporting
confidence: 86%
“…The main wear mechanism was abrasion wear [17], causing crater wear resulting in final cutting edge failure. Similar wear mechanisms were observed by the authors in references [18,19] in high speed machining of hardened steel. W.Y.H.…”
Section: Introductionsupporting
confidence: 86%
“…The cross-sections of the chips were prepared through embedding and polishing. Each test was conducted once, since previous work 7) with similar cutting tests shows the standard deviation in the test is expected to be small. The depth of cut of 0.1 mm was small against the nose radius of the tool of 1.2 mm.…”
Section: Cutting Test and Analysis Methodsmentioning
confidence: 99%
“…5) Another study has revealed that ceramic binders are better than metal binders in terms of adhesive wear resistance. 6) Regarding the influence of workpiece material composition on tool life, Ånmark et al 7) reported that when Ca-treated hardened steel is cut, multiple protective oxide layers of (Mn, Ca)S and (Ca, Al)(O, S) are formed on the tool, resulting in improved tool life. In addition, in the case where the work material is other than hardened steel, some researchers have reported that when cast iron is cut using a CBN tool, high Si content in the workpiece increases tool wear because Si in the workpiece reacts with Al in the tool binder, which changes the binder into SiAlON with low high-temperature strength.…”
Section: Effect Of Si In Workpiece Materials On Tool Wear In Hard Turningmentioning
confidence: 99%
“…3,4) Therefore, the machinability of steel is dependent on the characteristics of the workpiece, the cutting tool, and the machining parameters. 5,6) Chinchanikar et al 7) investigated the machinability of AISI 4340 steel with different levels of hardness. For the harder workpiece, higher cutting force but a better surface finish was observed.…”
Section: Introductionmentioning
confidence: 99%